Theory of Planned Behavior on the Determinants of Participation in the Long-Term Contraceptive Method Among Women of Reproductive Age, in Nganjuk, East Java - Joeliatin -; Bhisma Murti; Nunuk Suryani (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Unintended pregnancies remain a substantial global public health issue despite considerable advances in contraceptive technologies. The global trend shows that the use of permanent contraception to prevent unintended pregnancy is high. Although the trend also shows a rise in the use of long-acting reversible methods, these are still underutilized despite having contraceptive as well as non-contraceptive benefits. This study aimed to examine the determinants of participation in long-term contraceptive method among women of reproductive age in Nganjuk, East Java, using Theory of Planned Behavior.Subjects and Method: This was an analytic observational study, using case control design. This study was conducted in Bagor, Nganjuk, East Java. A total of 100 women of reproductive age was selected for this study by fixed disease sampling. The independent variables were constructs in the Theory of Planned Behavior, i.e. attitude, subjective norm, and perceived behavior control. The dependent variables were intention and participation in long-term contraceptive use. The data were collected by a set of questionnaire, and analyzed by path analysis.Results: Intention had direct and positive effect on participation in long-term contraceptive use (b=2.07; CI 95% 0.78-3.36; p=0.002). Attitude (b=1.40; CI 95% 0.41-2.40 p=0.006), subjective norm (b=1.64; CI 95% 0.76-2.53; p<0.001), and perceived behavior control (b=1.22; CI 95% 0.32-2.12; p=0.008) had indirect positive effect on participation in long-term contraceptive use through intention. Conclusion: There are direct and indirect effect of Theory of Planned Behavior constructs on participation long-term contraceptive use among women of reproductive age.Keywords: Theory of Planned Behavior, long-term contraceptive method, women of reproductive ageCorrespondence: Joeliatin. School of Midwifery, AKBID Wiyata Mitra Husada, Kertosono, Nganjuk, East Java. Email: yulisuyitno77@gmail.com.Journal of Health Promotion and Behavior (2016), 1(3): 171-179https://doi.org/10.26911/thejhpb.2016.01.03.04